Zāļu datu aizsardzības formulas ieviešanas tiesiskās problēmas. - Dumbrovska, Liene (Latvijas Universitāte, 2012)
„The new formula of data protection” – 8 years + 2 years + 1-3 years from practial point of view is analized in this thesis. The author explores the problem whether it is possible to use the medicine in 2014, when the reference medicine product has not ended according to new rules and how big is the opportunity to use it in the future. Before implementation of this formula, the problem mentioned problem did not arise. From the point of view of the author the formula in general is good, but it is also necessary to do some additional changes in the rules to make it complete. The author deals with original and abridged application medicinal product manufacturers and state institutions which hinder fair competition on the medicine market and some particular suggestions on how such problems can be solved. The author analyzes foreign and Latvian experience in this area. This work offers suggestions how these problems can be solved nowadays and in the future on the medicinal market in order to secure a fair competition and granting that medicinal products will be authorised in accordance with legal regulations.
The legal issues of implementation of the data exclusivity formula of medicinal products.
Keywords: Juridiskā zinātne